Pulmonary vessel volume can help to differentiate fibrotic lung diseases - Gökçek, Atila (The European Research Journal, 2023)
Objectives: Idiopathic pulmonary fibrosis (IPF), non-specific interstitial pneumonia (NSIP), and chronic hypersensitivity pneumonitis (CHP) are diffuse fibrosing lung diseases that are sometimes difficult to differentiate by only visual evaluation of CT images. We aimed to find if pulmonary vessel volume (PVV), a new quantitative CT measure, can help to differentiate these diseases at the time of diagnosis. Methods: We retrospectively measured PVV values of IPF, NSIP, and CHP patients diagnosed within the last five years in our institution, by using their CT images at the time of diagnosis. We used CALIPER-technology (Computer-Aided Lung Informatics for Pathology Evaluation and Rating) for the quantification of CT images. We compared the PVV values of disease groups by the Kruskal-Wallis test and performed ROC curve analysis to evaluate the ability of PVV to differentiate these diseases. Results: We measured the PVV values of 152 patients, 113 of them were diagnosed with IPF, 16 with NSIP, and 23 with CHP. The PVV value of the NSIP group was significantly lower than that of both IPF (p = 0.028) and CHP (p = 0.013) groups. However, there was no significant difference between IPF and CHP groups (p = 0.924). Selected cut-off values of PVV were found to differentiate NSIP from IPF with a specificity of 88%, and NSIP from CHP with a specificity of 91%. Conclusions: PVV measured by CALIPER at the time of diagnosis can help to differentiate NSIP from both IPF and CHP.